1998
DOI: 10.1093/hmg/7.11.1779
|View full text |Cite
|
Sign up to set email alerts
|

CAG Repeat Expansion in Autosomal Dominant Familial Spastic Paraparesis: Novel Expansion in a Subset of Patients

Abstract: Autosomal dominant familial spastic paraplegia (FSP) is a genetically heterogeneous neurodegenerative disorder displaying anticipation for which three loci have been mapped to the chromosomal positions 14q11.2-q24.3 (SPG3), 2p21-p24 (SPG4) and 15q11.1 (SPG6). The repeat expansion detection (RED) method has been used to demonstrate expanded CAG repeats in some FSP families that map to SPG4. We analyzed 20 FSP families, including four for which there is evidence for linkage to SPG4, and found that in most cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Recently, Benson et al (1998) analyzed 20 AD-HSP families with the RED method, including 4 kindreds showing linkage to the SPG4 locus, and demonstrated that most repeat expansions detected by this technique were caused by nonpathogenic expansions of the chromosome 18q21.1 SEF2-1 (Breschel et al, 1997) and 17q21.3 ERDA1 (Nakamoto et al, 1997) loci. However, a novel CAG repeat expansion was suggested to be the cause of the disease in 6 of the 20 families studied (Benson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Benson et al (1998) analyzed 20 AD-HSP families with the RED method, including 4 kindreds showing linkage to the SPG4 locus, and demonstrated that most repeat expansions detected by this technique were caused by nonpathogenic expansions of the chromosome 18q21.1 SEF2-1 (Breschel et al, 1997) and 17q21.3 ERDA1 (Nakamoto et al, 1997) loci. However, a novel CAG repeat expansion was suggested to be the cause of the disease in 6 of the 20 families studied (Benson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Anticipation (increasing disease severity or decreasing age at onset in subsequent generations) is a feature of such diseases, and reflects the fact that the CAG repeat expansion may increase in size from generation to generation [56]. Anticipation has been described for SPG4-and SPG3-linked ADPHSP families, and recent molecular genetic data suggest that CAG repeat expansions are implicated in SPG4-linked ADPHSP [24,43,[53][54][55][59][60][61]. However, a conclusive answer as to whether trinucleotide repeat expansions are involved is likely to require cloning of the responsible genes.…”
Section: Autosomal Dominant Pure Hspmentioning
confidence: 99%
“…Previous studies using the RED technique are difficult to interpret since CTG18.1 and ERDA1 account for a large portion of the RED products. 10,19,21 There is some evidence for the involvement of ERDA1 in bipolar disorder. Verheyen et al 19 reported a significantly larger proportion of bipolar patients carrying one or two ERDA1 alleles Ͼ40 repeats with a negative correlation between age of onset and CAG/CTG length in the offspring of eight BP pedigrees.…”
mentioning
confidence: 99%